In Vivo Evaluation of [Gly14]-Humanin's Protective Effect Against Cisplatin-Induced Ototoxicity - Yaşar, Murat; Gökmen, Sedat; Atalay, Fatma; Çınar, İrfan; Aydin, Yusuf; Tatar, Musa (The European Research Journal, 2026)
Objectives: This study aimed to evaluate in vivo the potential protective effects of [Gly14]-humanin against cisplatin-induced ototoxicity (CIO) and its modulatory effects against oxidative stress, inflammatory, and apoptotic markers Methods: Thirty-five male Balb/c mice were randomly divided into five groups: control, cisplatin, cisplatin + [Gly14]-humanin (3 mg/kg), cisplatin + (6 mg/kg), and vitamin E. Cisplatin (10 mg/kg, b.w.) was administered as a single dose. [Gly14]-humanin was administered intraperitoneally for 14 days. Biochemical analyses (Superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA)), gene expression levels (TNF-α, IL-1β, IL-6, CASP-3, CASP-9, Bcl-2/Bax), and histopathological examinations (PARP1, PARP2 immunoreactivity) were performed in cochlear tissue samples to evaluate oxidative stress, inflammation, and apoptosis. Results: Cisplatin decreased SOD and GSH levels and increased MDA levels in the cochlear tissue (P